Variation in wood properties of 26-year-old Handroantus impetiginosus cultivated in Luiz Antônio, SP - Santos, Camila Moura; Romeiro, Diego; Amorim, Erick Phelipe; Longui, Eduardo Luiz; Lima, Israel Luiz de (Scientific Electronic Archives, 2022)
Provenance testing can provide information on silvicultural behavior and wood quality of species for selection of genetic material for different locations and conservation of the genetic base. The aim of this work was to study the longitudinal variation of basic density, volumetric shrinkage and microfibril angle of wood from two provenances (Assis and Bauru) of Handroantus impetiginosus planted in Luiz Antonio SP. After 26 years of planting, twelve trees were felled, six from each provenance. According to the results obtained, it could be concluded that the analysis of variance (ANOVA) showed that for the provenance there was a significant variation for the volumetric shrinkage of the wood and for basic wood density and microfibril angle the significance of variation did not occur. The basic wood density varied significantly between the different positions, at the height of the tree and for volumetric shrinkage, and for the microfibril angle it did not occur. There is a positive relationship between tree height and basic wood density of wood, for Assis and Bauru provenances.